Try working from the inside out. That is, start with
and convert one step at a time. The first step would be
Can you continue?
This problem asks me to use the p→q ≡~pvq and p↔q≡(~pvq) ^ (~qvp) to rewrite the given statement forms without using the symbol → or ↔.
The problem is (p→(q→r)) ↔ ((p^q)→r)
Using a bunch of truth tables and kinda just guessing I was able to come up with ~(~pv(~qvr)) v (~(p^q)vr) or (~pv(~qvr)) v ~(~(p^q)vr), both of which would work I think but I am not 100% sure they are correct so if someone wants to double check them that would be good. I think there is a quicker way to do this but the logical equivalence that I should use isn't really obvious to me just looking at a problem that complex. I guess I'm just asking for some tips on how to do this so any help would be appreciated.